Active matrix metalloproteinase‐8 and periodontal bacteria depending on periodontal status in patients with rheumatoid arthritis. (21st March 2017) - Kirchner, A.; Jäger, J.; Krohn‐Grimberghe, B.; Patschan, S.; Kottmann, T.; Schmalz, G.; Mausberg, R. F.; Haak, R.; Ziebolz, D.
Abstract : Background and Objectives: The aim of this clinical cross‐sectional study was to determine the level of active matrix metalloproteinase‐8 (aMMP‐8) and periodontal pathogenic bacteria in gingival crevicular fluid in patients with rheumatoid arthritis (RA) with varying periodontal conditions. Material and Methods: In total, 103 patients with RA and 104 healthy controls (HC) were included. The assessment of periodontal status included periodontal probing depth, bleeding on probing and clinical attachment loss. Periodontal disease was classified as healthy/mild, moderate or severe. For the determination of aMMP‐8 levels using enzyme‐linked immunosorbent assay and periodontal pathogenic bacteria using polymerase chain reaction, samples of gingival crevicular fluid were taken from the deepest gingival pockets. The statistical analyses used included a Mann–Whitney U ‐test, a chi‐squared test or a Fisher's exact test, and the significance level was set at α = 5%. Results: We found that 65% of patients with RA and 79% of HC had moderate to severe periodontal disease ( p = 0.02). The prevalence of periodontal pathogens was almost equal ( p > 0.05). Furthermore, depending on periodontal disease severity only minor differences in bacterial prevalence were detected. With increasing severity of periodontal disease, higher aMMP‐8 levels were observed. Accordingly, a significant difference in patients with moderate periodontal disease (RA: 15.3 ± 13.8; HC: 9.1 ± 9.1; p ≤ 0.01) and severe periodontal disease (RA: 21.7 ± 13.3; HC: 13.1 ± 8.6; p = 0.07) was detected, with a greater tendency in the latter group. Conclusion: The increased aMMP‐8 levels in the RA group indicate that the presence of RA appears to have an influence on the host response at a comparable level of bacterial load and periodontal disease severity.